Our Neurotic Culture, Reclaimed (KULT_online, 2019)
The mission of this essay collection is to uproot neurosis from its original medical and psychoanalytical bedrock and embed it within contemporary critical cultural and literary discussions. Through reading neurosis in culture and fiction, it tests its subversive potential for stretching the boundaries of normalcy. The eight chapters encompass an impressive range of texts, and a sizable portion thereof investigate neurosis in a post-colonial context, especially through the work of Frantz Fanon. Still, it is the chapters that decipher a poetics of neurosis in political discourses of neoliberal governmentality and right-wing populism that deliver an important interpretative and culturally relevant punch. Overall, A Poetics of Neurosis paves new roads for the medical humanities and delivers successfully on its goal to disturb notions of normalcy and deviation in our global cultural climate.